(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Introduction: Radioactive iodine (RAI) ablation is a well-established treatment modality for differentiated thyroid carcinoma (DTC). The Institute of Nuclear Medicine and Allied Sciences (INMAS), Rajshahi, has been providing RAI therapy for several years, and its management protocol was upgraded in 2015 by the Society of Nuclear Medicine Bangladesh. The objectives of this study were to assess the long-term outcome of RAI ablation in patients with DTC, evaluate therapeutic response in iodine-avid metastases, and determine the disease-free status of patients after treatment. Materials and Methods: This retrospective study included 257 patients diagnosed with DTC who received RAI ablation between January 2015 and December 2017 at INMAS, Rajshahi. All patients had previous surgical treatment. Based on risk stratification, low-risk patients received 30–100 mCi of iodine-131, while intermediate and high-risk patients received doses greater than 100–200 mCi. Follow-up assessment included diagnostic whole-body scintigraphy, serum thyroglobulin (Tg), anti-thyroglobulin antibody (anti-Tg Ab), and high-resolution ultrasound (HRUS) of the neck. Treatment response was categorized as complete response (CR) or persistent disease (PD). Results: Among the 257 patients, 89 (34.63%) were male and 168 (65.37%) were female. Five patients were lost to follow-up. Papillary carcinoma accounted for 235 cases (93.25%) while follicular carcinoma accounted for 17 cases (6.74%). After one year, 231 patients (89.68%) were disease-free based on negative imaging and biochemical markers. Twenty-one patients required additional evaluation or therapy due to residual tissue or metastases. After an average follow-up of five years, complete response was observed in 239 patients (94.84%) while persistent disease or recurrence occurred in 13 patients (5.16%). Conclusion: RAI ablation is highly effective for achieving disease control in patients with DTC, particularly in iodine-avid locoregional disease. However, patients with iodine non-avid metastases show limited response and require alternative therapeutic strategies. Bangladesh J. Nuclear Med. 28(2): 303-308, July 2025